A responsabilidade tributária das plataformas digitais - Dallacosta, Victor Schleder (2025)
This paper is the result of a study on the application of general rules on tax liability and state rules that establish the tax liability of controllers of digital e-commerce platforms. From the very first pages, it is clear that, because they are directly associated with the evolution of information technologies, digital platforms are presented to the law as an atypical structure that concretizes legal transactions entered into by third parties. The power to influence and moderate social relations attracted the interest of state agencies to digital platforms, which saw them as a powerful instrument for monitoring and collecting taxes. In order to stop the erosion of tax bases, 18 of the 26 Brazilian states included in their state legislation legal rules that aim to hold controllers of digital platforms liable for the payment of ICMS. In the broad study of the rules of the constitutional tax system, the compatibility of the rules introduced by the federated entities (states) with the rules of higher hierarchy was assessed. In the end, it is concluded that it is possible to hold the controllers of digital platforms liable for the payment of the tax, provided that the platforms have control over the commercial operation and have failed to comply with a duty of cooperation